Aortic to caudal vena cava ratio measurements using abdominal ultrasound are increased in dogs with confirmed systemic hypertension. Issue 2 (16th December 2019) - Holland, Merrilee; Hudson, Judith; Bao, Yida; Gaillard, Philippe
Abstract: Chronically sustained systemic hypertension in dogs can damage the kidneys, eye, brain, heart, and vessels. In human medicine, systemic hypertension has been implicated as the most common risk factor for aorta dilation, which can progress to an aneurysm. Abdominal ultrasound has been commonly used to monitor the size of the abdominal aorta in people with systemic hypertension. In this retrospective cross‐sectional abdominal ultrasound study, evaluation of the size of the abdominal aorta relative to the caudal vena cava was performed in 18 control dogs and 128 dogs with confirmed systemic hypertension. Preexisting conditions contributing to systemic hypertension in these dogs were renal disease, hyperadrenocorticism, diabetes mellitus, adrenal tumors, and previous administration of phenylpropanolamine or palladia. The abdominal aorta and caudal vena cava were assessed from longitudinal images cranial to the trifurcation with measurements made from outer border to outer border of the walls, being careful not to compress the caudal vena cava that would alter its size. Our hypothesis was the ratio of the diameter of the abdominal aorta to caudal vena cava would be higher in dogs with systemic hypertension compared to dogs with normal blood pressure. The mean abdominal aorta‐caudal vena cava ratio was 1.028 in control dogs with a normal blood pressure and 1.515 in dogs with systemic hypertension. In dogs with confirmed systemic hypertension, the abdominal aorta was dilated compared to the caudal vena cava in the caudal abdomen. An increase in the abdominal aorta‐caudal vena cava ratio in a dog should raise suspicion for the presence of systemic hypertension and prompt evaluation of blood pressure.